The Cosmology of Sedulur Traditional House Attitudes to the Realization of Local Wisdom for the Survival of Harmonization of Life - Khoirina, Nisa; Fidiyani, Rini (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The cosmology of the Sedulur Sikep traditional house in Pati Regency is studied in depth in this study as an expression of local wisdom that is crucial for the continuation of a harmonious life. Motivated by.Purposes of the Research: Seeks to determine why this cosmology is necessary in this particular context and to examine how the cosmology of the Sedulur Sikep traditional house is an expression of local wisdom for the harmonious survival of life.Methods of the Research: This study uses a qualitative descriptive approach with a sociological juridical research type. Applying the theory of legal pluralism to examine how customary law (also known as living law) interacts with state law and cultural anthropology theory to understand how cosmology manifests itself in the tangible and intangible elements of customary houses. Interviews and observations were used to collect primary data, which was then supported by secondary and tertiary data. Triangulation is used to ensure the validity of the data.Results Main Findings of the Research: Each component of the Sedulur Sikep traditional house reflects a worldview that encourages the creation of harmony between humans, nature, and spirituality. This cosmology functions as a living law that encourages the creation of ecological harmony, social solidarity (the principle of seduluran), and inner peace. This is important for the urgency of community sustainability as an identity, social control system, and foundation of cultural resilience in the face of legal pluralism and globalization.